2005
DOI: 10.1097/01.ccm.0000186759.13325.dc
|View full text |Cite
|
Sign up to set email alerts
|

Marked synergism between vasopressin and angiotensin II in a human isolated artery

Abstract: These results indicate that there is a powerful synergism between the contractile effects of low-dose VP and AII in this human isolated artery. Moreover, the elevations of plasma AII and VP levels during hemorrhage suggest that this synergism may be both physiologically and clinically important in optimizing vasoconstriction and maintaining blood pressure in such critical states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…22). Our initial studies determined that responses to 30 pM and 10 nM AVP would not be altered by prior exposure to 30 pM AVP (data not shown).…”
Section: Acute Vasoconstriction Induced By 30 Pm and 10 Nm Avpmentioning
confidence: 99%
“…22). Our initial studies determined that responses to 30 pM and 10 nM AVP would not be altered by prior exposure to 30 pM AVP (data not shown).…”
Section: Acute Vasoconstriction Induced By 30 Pm and 10 Nm Avpmentioning
confidence: 99%
“…The present findings demonstrate that Ang II increases CCSM contraction as a pathological consequence of PBOO. We have used only one concentration of Ang II on each individual tissue strip as multiple application of Ang II to isolated human arteries results in a marked desensitization of the functional response (i.e., tachyphylaxis) [24]. This phenomenon may explain the large variation in the Ang II 10 -5 M error bar following PBOO (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that sympathetic denervation of the rat tail artery greatly increases the responsiveness of the isolated artery to ANG II and vasopressin by 2 wk after denervation (32). Both ANG II and vasopressin are significantly elevated during hypotensive hemorrhage and could conceivably provide a greater contribution to the maintenance of arterial pressure during prolonged hemorrhage in the denervated animal due to a similar denervation-induced supersensitivity to noncatecholamine vasopressor agents (13), although this possibility remains to be studied.…”
Section: Splanchnic Nerve Control Of Arterial Pressure During Hemorrhagementioning
confidence: 98%